Dynamique de gestion de la biodiversité d’igname face au développement du vivrier marchand au nord-Bénin - Janvier Egah; Mohamed Nasser Baco; Ismail Moumouni (VertigO, 2012)
In this paper, we analyzed the impact of the development of food market on the dynamic of yam biodiversity management in Northern Benin, using a mix-method approach. We conducted investigations in Tchaourou district, which is the yam barn in Benin. Three villages were selected according to the degree of isolation and market development. Our sample included 90 farms, 30 per village. We collected data on yam cultivation (cultivated varieties, most expensive varieties, farming systems), and the use of yam production (household consumption, marketing, donations and seed) through focus groups, and informal, unstructured individual interviews. Mean comparison tests showed that farmers who produced yam mostly for market cultivated more varieties that the others. In addition, the allocation of large amount of land to high commercial value varieties of yam did not impact on the diversity of yam. In conclusion, the development of food market did not affect yam biodiversity. However, steps may be taken to prevent the lost of yam biodiversity due to market-driven production.